Neurologic outcomes following the introduction of a policy for using soft cervical collars in suspected traumatic cervical spine injury: A retrospective chart review. (9th October 2020) - Asha, Stephen E; Curtis, Kate; Healy, Georgina; Neuhaus, Lauren; Tzannes, Alexander; Wright, Kelly
Abstract: Objective: In trauma patients with potential cervical spine injury, immobilisation with a rigid cervical collar is widely recommended to prevent a secondary spinal cord injury. There is a lack of evidence for the effectiveness of this practice, but increasing evidence for complications from rigid collars. Soft foam collars may mitigate some of these issues and are used in our health service in place of rigid collars in selected patients at risk for traumatic cervical spine injury. The objective of the present study was to describe the neurological outcome of patients according to the cervical stabilisation technique used. Methods: A multi‐centre, retrospective, consecutive, case series of all patients assessed for a traumatic cervical spine injury from October 2017 to July 2018 was conducted. Data were obtained by a medical chart review. The primary outcome was the development of a new neurological deficit because of spinal cord injury while in hospital. Results: Inter‐rater reliability of data abstraction demonstrated very strong agreement (kappa 0.85, 95% confidence interval 0.80–0.90). Of 2036 patients, 1133 were managed in a soft collar. A new neurological deficit because of spinal cord injury developed in two patients managed in a rigid collar. One case managed in a soft collar was uncertain because of an incomplete baseline neurological examination. Conclusion: The use of soft foam cervical collars in patients at risk for a cervical spine injury does not appear to increase the risk for secondary spinal cord injury but larger prospective studies are required before a robust conclusion on safety can be claimed. Abstract : In trauma patients with potential cervical spine injury, immobilisation with a rigid cervical collar is widely recommended to prevent a secondary spinal cord injury, despite a lack of evidence for this practice, but increasing evidence for complications. Soft foam collars may mitigate some of these issues and do not appear to increase the risk for secondary spinal cord injury. Larger prospective studies are required before a robust conclusion on safety can be claimed.